Diferensiasi Tugas Pokok dan Fungsi Lembaga Perwakilan Bikameral dalam Konteks Keadilan - Myaskur; Wahyudiono, Tri (Universitas Pangeran Diponegoro Nganjuk, 2025)
This study analyzes the differentiation of main duties and functions of bicameral representative institutions in the context of justice in Indonesia. Indonesia's legislative system comprises the House of Representatives (DPR) and the Regional Representative Council (DPD), each with distinct roles and authorities. The DPR holds legislative, budgeting, and oversight functions, while the DPD is involved in proposing and discussing bills related to regional autonomy, central-regional relations, and natural resource management. However, the DPD's role is often perceived as less effective in the legislative function. This study employs a normative approach with descriptive analysis to evaluate the balance of roles between these two institutions in achieving representative justice. The findings indicate the need to strengthen the DPD's functions to create a more equitable and balanced representation system in the national legislative process.